Hunting for hidden gold - Dixon, Franklin W. (New York Grosset & Dunlap, 1991)
Timber wolves, a Rocky Mountain blizzard, and a mine cave-in are only a few of the perils Frank and Joe Hardy encounter during their search for the principal members of a notorious gang responsible for a payroll robbery.
Keywords: Hardy, Joe (Fictitious character) -- Juvenile fiction; Hardy, Frank (Fictitious character) -- Juvenile fiction; Detective and mystery stories -- Juvenile fiction; Mystery and detective stories